England after the Great Recession - Preston, P. W. author. aut Link
VII, 223 p.
Keywords: An exploration of the recent financial crisis which argues that the hitherto dominant intellectual and policy paradigm of neo-liberalism has been fatally weakened and will in due course be replaced. The implications of the crisis for politico-cultural identities and our sense of ourselves as members of an ordered society are explored.